Durability and flexural behavior of concrete-filled hybrid GFRP beams with various interface treatments under humid environmental exposure - Tuna Ülger; Murat Cavuslu (Case Studies in Construction Materials)
This study presents an experimental investigation into the long-term flexural behavior and interface shear failure mechanisms of Concrete-Filled Hybrid Glass Fiber Reinforced Polymer (CF-GFRP) beams exposed to humid environmental conditions. The research primarily focuses on enhancing the bond efficiency at the concrete–GFRP interface using different surface treatment techniques aimed at improving load transfer and mitigating premature debonding. The mechanical properties of the constituent materials - including concrete, GFRP profiles, and bonding adhesives—were comprehensively characterized through laboratory testing. A series of three-point bending tests were conducted on a reference GFRP box beam and four hybrid beam specimens, each incorporating a unique surface treatment strategy: natural bonding (untreated), granular coating, epoxy adhesive, and mechanical fastening. Both short-term performance (after 30 days of curing) and long-term durability (following two years of exposure to uncontrolled outdoor conditions) were assessed. The findings revealed that, except for the naturally bonded specimens, the beams retained a significant portion of their flexural capacity over time, with only moderate reductions observed. Among all configurations, the epoxy-bonded beam exhibited the highest initial flexural strength; however, it also demonstrated the greatest performance degradation under environmental exposure, highlighting the critical influence of environmental durability on bonded interfaces. Detailed observations of crack initiation, propagation, and final failure modes emphasized the importance of optimized surface preparation and mechanical interlocking in promoting structural integrity and long-term serviceability of CF-GFRP beams.